2018
DOI: 10.1093/carcin/bgy045
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the lysyl oxidase propeptide domain accelerates carcinogen-induced cancer

Abstract: The propeptide (LOX-PP) domain of the lysyl oxidase proenzyme was shown to inhibit the transformed phenotype of breast, lung and pancreatic cells in culture and the formation of Her2/neu-driven breast cancer in a xenograft model. A single nucleotide polymorphism (SNP, rs1800449) positioned in a highly conserved region of LOX-PP results in an Arg158Gln substitution (humans). This arginine (Arg)→glutamine (Gln) substitution profoundly impaired the ability of LOX-PP to inhibit the invasive phenotype and xenograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Lan Ma et al. found that another SNP of LOX (rs1800449) was associated with the susceptibility to coronary artery diseases in Chinese population ( 37 ) and a recent mouse model also suggested that the missense mutation ( p .G473A) caused by rs1800449 could lead to loss tumor suppressor function of the LOX propeptide and thus accelerate carcinogen-induced tumor formation ( 38 ). However, this SNP was not found to be associated with IA in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Lan Ma et al. found that another SNP of LOX (rs1800449) was associated with the susceptibility to coronary artery diseases in Chinese population ( 37 ) and a recent mouse model also suggested that the missense mutation ( p .G473A) caused by rs1800449 could lead to loss tumor suppressor function of the LOX propeptide and thus accelerate carcinogen-induced tumor formation ( 38 ). However, this SNP was not found to be associated with IA in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the impact of genetic alteration, an Arg158Gln substitution in LOX-PP has been shown to be associated with susceptibility of breast [ 71 ], lung [ 72 ], colorectal [ 73 ], and ovarian cancer [ 74 ]. Cueva et al showed that in knock-in strain LOX-PP Gln mice that harbor an Arg152Gln substitution, corresponding to the human Arg158Gln polymorphism of LOX-PP, manifest increased susceptibility to carcinogen-induced breast cancer and hepatic inflammation compared to their wild type counterparts [ 75 ]. With reference to the epigenetic episode, Shao et al demonstrated that 5-azacytidine (5-aza-CR), acting on hypomethylation of DNA by inhibiting DNA methyltransferase, induces LOXL4 upregulation and triggers LOXL4-depedent cell apoptosis in HCC [ 58 ].…”
Section: Regulatory Pathways At Various Sub-cellular Levels and Thmentioning
confidence: 99%
“…Furthermore, the findings indicated that the observed positive prognostic effect of LOX was associated, at least in part, to miR-30b regulation, confirming the conclusions by Zhong et al ( 64 ) regarding a central role of this miRNA in NSCLC suppression. However, the impact of LOX remains incompletely clear; it is possible that there exists multiple forms of LOX proteins ( 65 ), and it is not known whether the signalling components downstream of LKB1 , including LOX , may be involved in an LKB1 -independent manner; further studies will be required to reach a conclusive point.…”
Section: Discussionmentioning
confidence: 99%